In Saccharomyces cerevisiae the attenuation of the 2- deoxy-D-glucose toxicity is alleviated by inositol - Ravi, Chidambaram; Nachiappan, Vasanthi (International Journal of Scientific Research in Biological Sciences, 2018)
In Saccharomysis cerevasiae the glycolytic transcription factor GCR1 tightly controls the expression of genes involved in glycolysis but the importance of Gcr1 transcription in 2-DG toxicity is still elusive. In the present study, we observed 2-DG toxicity in the wild-type, gcr1∆, and ino2∆ cells under inositol absence (I−) condition obstruct the growth, hence the opi1∆ cells were resistant to 2-DG exposure. Further, the presence of 2-DG significantly decreased the promoter activity of INO1 in the WT cells. The 2-DG exposure suppressed the growth rate in WT and gcr1∆ strains under inositol limitation condition, but the opi1∆ (over production of inositol) strain was resistant to the 2-DG exposure with I− condition. Taken together, the above findings suggest that 2-DG exposure reduced the promoter activity of INO1 leads to inositol auxotrophic growth defect, hence the inositol supplementation bring back normal. To conclude that the inositol alleviates the 2-DG toxicity in Saccharomyces cerevisiae.